Amino acids effects on heterocyclic amines formation and physicochemical properties in pan‐fried beef patties. Issue 4 (9th March 2020) - Linghu, Ziyi; Karim, Faris; Taghvaei, Mostafa; Albashabsheh, Zaher; Houser, Terry A.; Smith, J. Scott
Abstract: The effects of surface application of amino acids on the formation of heterocyclic amines (HCAs) and meat quality properties were evaluated in pan‐fried beef patties (230 °C/15 min). Tryptophan, lysine, leucine, and proline at three concentrations, 0.05%, 0.20%, and 0.50% (w/w), were tested. The meat crusts were analyzed for HCA content using liquid chromatography‐tandem mass spectrometry. Results showed that surface application of all tested amino acids significantly reduced total HCA content ( P < 0.05), and the interaction of amino acid type and concentration significantly affected ( P < 0.05) both individual and total HCA formation. Tryptophan at 0.50% reduced total HCAs the most (0.92 ng/g, 93% inhibition), followed by 0.50% lysine (1.94 ng/g, 84% inhibition), while leucine (3.95 ng/g, 64% inhibition) and proline (4.71 ng/g, 56% inhibition) were less effective at 0.50%. In addition, applying amino acids to meat surface significantly influenced ( P < 0.05) pH and surface color change of beef crusts; particularly, lysine at 0.20% and 0.50% increased pH and a * (redness) but reduced b * (yellowness), while tryptophan and leucine at 0.50% increased L * (whiteness). No significant effect was observed on cooking loss. Adding amino acids at 0.50% affected ( P < 0.05) formation of aldehydes and pyrazines (as the key flavor compounds of fried beef). Overall, the results of this study suggested that adding amino acids to ground beef patties could effectively mitigate mutagenic HCA formation during cooking.